A Candidate Regulatory Variant at the TREM Gene Cluster Confer Alzheimer’s Disease Risk by Modulating Both Amyloid-β Pathology and Neuronal Degeneration - Tian, Mei-Ling; Ni, Xiao-Neng; Li, Jie-Qiong; Tan, Chen-Chen; Cao, Xi-Peng; Tan, Lan; , for the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2019)
Abstract Background: Rs9357347 located at the triggering receptor expressed on myeloid cells (TREM) gene cluster could increase TREM2 and TREM-like transcript 1 (TREML1) brain gene expression, which is considered to play a protective role against Alzheimer’s disease (AD). Objectives: To investigate the role of rs9357347 in AD pathogenesis by exploring the effects of rs9357347 on AD specific biomarkers. Methods: This study analyzed the association of rs9357347 with AD-related cerebrospinal fluid (CSF) and neuroimaging markers from 201 cognitively normal (CN) older adults, 349 elders with mild cognitive impairment (MCI), and 172 elders with AD dementia from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). We next analyzed the association in 259 amyloid-β positive (Aβ+) elders and 117 amyloid-β negative (Aβ-) elders (Aβ+: CSF Aβ1-42 ≤ 192pg/ml; Aβ-: CSF Aβ1-42 > 192pg/ml). Associations were tested using multiple linear regression models at baseline. Furthermore, multiple mixed-effects models were used in a longitudinal study which lasted 4 years. Results: At baseline, we found that rs9357347 had association with CSF Aβ1-42 in CN group (β = 0.357, P=0.009). In AD group, rs9357347 was associated with total tau (T-tau) level (β = -0.436, P = 0.007). Moreover, the strong influence exerted by rs9357347 on T-tau was also seen in Aβ+ group (β = -0.202, P = 0.036). In the longitudinal study, rs9357347 was also found to be associated with Aβ1-42 in CN group (β = 0.329, P= 0.023). In AD group, the mutation of rs9357347 was associated with slower accumulation of T-tau (β = -0.472, P = 0.002) and tau phosphorylated at threonine 181 (P-tau 181 [β = -0.330, P = 0.019]). Furthermore, the obvious influence exerted by rs9357347 on T-tau was also seen in Aβ+ group (β = -0.241, P = 0.013). Conclusion: This study suggested that rs9357347 reduced the risk of AD by modulating both amyloid-β pathology and neuronal degeneration.